Regulation of gap junction conductance by calcineurin through Cx43 phosphorylation: implications for action potential conduction - Jabr, Rita I. (2016)
Cardiac arrhythmias are associated with raised intracellular [Ca2+] and slowed action potential conduction caused by reduced gap junction (GJ) electrical conductance (Gj). Ventricular GJs are composed of connexin proteins (Cx43), with Gj determined by Cx43 phosphorylation status. Connexin phosphorylation is an interplay between protein kinases and phosphatases but the precise pathways are unknown. We aimed to identify key Ca2+-dependent phosphorylation sites on Cx43 that regulate cardiac gap junction conductance and action potential conduction velocity. We investigated the role of the Ca2+-dependent phosphatase, calcineurin. Intracellular [Ca2+] was raised in guinea-pig myocardium by a low-Na solution or increased stimulation. Conduction velocity and Gj were measured in multicellular strips. Phosphorylation of Cx43 serine residues (S365 and S368) and of the intermediary regulator I1 at threonine35 was measured by Western blot. Measurements were made in the presence and absence of inhibitors to calcineurin, I1 or protein phosphatase-1 and phosphatase-2. Raised [Ca2 +]i decreased Gj, reduced Cx43 phosphorylation at S365 and increased it at S368; these changes were reversed by calcineurin inhibitors. Cx43-S368 phosphorylation was reversed by the protein kinase C inhibitor chelerythrine. Raised [Ca2+]i also decreased I1 phosphorylation, also prevented by calcineurin inhibitors, to increase activity of the Ca2+-independent phosphatase, PPI. The PP1 inhibitor, tautomycin, prevented Cx43-365 dephosphorylation, Cx43-S368 phosphorylation and Gj reduction in raised [Ca2+]i. PP2A had no role. Conduction velocity was reduced by raised [Ca2+]i and reversed by calcineurin inhibitors. Reduced action potential conduction and Gj in raised [Ca2+] are regulated by calcineurin-dependent Cx43-S365 phosphorylation, leading to Cx43-S368 dephosphorylation. The calcineurin action is indirect, via I1 dephosphorylation and subsequent activation of PP1.